Hydrogen Production from Aluminum Waste Using the Aluminum-Water Method with Potassium as Activator - Icha Amelia; Dedi Rohendi; Addy Rachmat; Nirwan Syarif; Dwi Hawa Yulianti; Nyimas Febrika Sya'baniah; Nurmalina Adhiyanti; Ory Adelia; Normah Normah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
Research on hydrogen production from aluminum waste using the aluminum-water method using potassium as an activator has been successfully carried out. This research aims to determine the performance of the potassium activator in hydrogen production with variable water volume and potassium percentage. Hydrogen gas production is carried out using 60 mesh aluminum waste. Optimum conditions were achieved when a mass of 1 gram of aluminum was reacted with an additional volume of water of 1.5 mL, and 7% w/w of the activator mass, with the production of hydrogen gas of 553 mL at a production rate of 69 mL/minute.